2001
DOI: 10.1016/s0002-9270(99)00826-6
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in acute intestinal vasculopathy mortality in France

Abstract: Awareness of higher risk during winter would help to reduce the high mortality from acute intestinal vasculopathy. A better understanding of this seasonal pattern would allow practitioners to improve early diagnosis and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
1
1
Order By: Relevance
“…Sheth et al (1999) have demonstrated a greater winter increase in mortality from acute myocardial infarction and stroke. Recently, seasonal variation peaking in winter in acute intestinal vasculopathy was demonstrated by Boulay et al (2001). Although there are data considering the difference between hGH and PRL level along with correlation with SOD activity in animal models (Bolzan et al, 1997), no correlation between SOD and pituitary hormones was observed in our study, despite the observed seasonal differences between SOD and pituitary hormones.…”
Section: Discussioncontrasting
confidence: 76%
“…Sheth et al (1999) have demonstrated a greater winter increase in mortality from acute myocardial infarction and stroke. Recently, seasonal variation peaking in winter in acute intestinal vasculopathy was demonstrated by Boulay et al (2001). Although there are data considering the difference between hGH and PRL level along with correlation with SOD activity in animal models (Bolzan et al, 1997), no correlation between SOD and pituitary hormones was observed in our study, despite the observed seasonal differences between SOD and pituitary hormones.…”
Section: Discussioncontrasting
confidence: 76%
“…It was proposed that venous ulcers resulted from local ischaemia due to the restriction of oxygen diffusion caused by pericapillary fibrin cuffs. 2,13 However, further studies with 133 Xe clearance revealed that these ulcers were not principally attributable to skin ischaemia and that fibrin cuffs were not a reflection of a thrombotic process, but a perturbed condition of the endothelium that permitted the passage of large molecules into the perivascular space. 10 An alternative theory -the leukocyte trapping hypothesis -claims that excessive leukocytic adhesion, migration and activation appear to underlie chronic venous insufficiency.…”
Section: Discussionmentioning
confidence: 99%